Aggregation-induced enhanced green light emission from a simple donor–π–acceptor (D–π–A) material: a structure–property relationship study. (28th November 2016) - Gupta, Vinod Kumar; Singh, Ram Adhar
Abstract : Organic D–π–A materials, possessing intramolecular charge transfer, have attracted much scientific attention in recent years because of their potential applications in the development of organic light emitting devices (OLEDs). Two new compounds, A1 andA2, having a D–π–A skeleton have been synthesized and single crystals were grown by the solution growth technique. Both compounds were characterized for crystallographic, thermal and photophysical properties. Upon photo-excitation in the solid state, A1 showed very strong green light emission whileA2 gave sky-blue emission with much lower intensity. A single crystal X-ray diffraction study revealed that in the crystal lattice ofA1, both the donor and acceptor groups are involved in the intermolecular interactions. This results in the restricted intramolecular rotation (RIR) of the D and A moieties, and enablesA1 to emit more intensely in the solid state due to aggregation-induced emission (AIE). Intense green light emission, along with a good crystalline nature indicates thatA1 might be a potential candidate for opto-electronic devices.